3(a+7)=-3(2a-1)

Simple and best practice solution for 3(a+7)=-3(2a-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(a+7)=-3(2a-1) equation:



3(a+7)=-3(2a-1)
We move all terms to the left:
3(a+7)-(-3(2a-1))=0
We multiply parentheses
3a-(-3(2a-1))+21=0
We calculate terms in parentheses: -(-3(2a-1)), so:
-3(2a-1)
We multiply parentheses
-6a+3
Back to the equation:
-(-6a+3)
We get rid of parentheses
3a+6a-3+21=0
We add all the numbers together, and all the variables
9a+18=0
We move all terms containing a to the left, all other terms to the right
9a=-18
a=-18/9
a=-2

See similar equations:

| 5v=–6+4v | | 11x-20=-19x-230 | | 0.6w-0.5=0.8w | | 3x=225/5x | | -x2-x-2=0 | | 4x+10=3x+56 | | 8x-32=-28 | | 12x-20=-19x-230 | | 4=3v+5 | | -10x+80=6x | | 4x+9=14x-91 | | 56=2n+99 | | 2×9=y-5 | | 2x-5=152x−5=15. | | 4n+21=2n+27 | | -9=6m+2m-1 | | -19n+9=-18n—12 | | 4x+9=14×-91 | | -1-(-4b-6)=-11+2b | | 3/8k-3/5+7/20=5/8 | | 5/6n-1/4n-1/2n=-2 | | -19n+9=-18n–12 | | 4s+s=200 | | -12x-9=6x+27 | | 1=0.1x-0.7-35 | | 6/5n+3/4=3/10 | | /3x-12=24 | | (x2–16)=48 | | 3(8p-6)=14 | | -10(x+5)+66=-17—-17 | | 13x+2=93 | | 157=-x+2 |

Equations solver categories